High-Throughput Screening of Kawasaki Disease Sera for Antiviral Antibodies. (9th May 2020) - Quiat, Daniel; Kula, Tomasz; Shimizu, Chisato; Kanegaye, John T; Tremoulet, Adriana H; Pitkowsky, Zachary; Son, MaryBeth; Newburger, Jane W; Elledge, Stephen J; Burns, Jane C
Abstract: Clinical features of Kawasaki disease (KD) display overlap with common pediatric viral illnesses, leading some to hypothesize that a viral infection is the inciting event for KD. To investigate viral infection history in KD patients, we performed comprehensive serological profiling using a high-throughput phage immunoprecipitation sequencing assay covering the complete reference protein sequences of known viruses with human tropism. KD and matched febrile control sera did not demonstrate differences in antiviral antibody profiles. We conclude that in the acute and subacute phases of disease, KD patients do not exhibit serologic evidence of exposure to known viruses that differs from controls. Abstract : High-throughput antibody profiling of acute sera from patients with Kawasaki disease demonstrates no evidence of a shared antibody response to known human viruses.